Average daily flow of microplastics through a tertiary wastewater treatment plant over a ten-month period. (15th October 2019) - Blair, Reina M.; Waldron, Susan; Gauchotte-Lindsay, Caroline
Abstract: Microplastics (MPs, <5 mm in size) are classified as emerging contaminants but treatment processes are not designed to remove these small particles. Wastewater treatment systems have been proposed as pathways for MPs pollution to receiving waters but quantitative and qualitative data on MP occurrence and transport remains limited, hindering risk assessment and regulation. Here, for the first time, the stepwise abundance and loading of MPs (60–2800 μm) in a tertiary wastewater treatment plant in the UK was assessed by sampling from May 2017 to February 2018. Microplastics were found in all sampling campaigns, with an average inflow of 8.1 × 10 8 (95% CI, 3.8 × 10 8 to 1.2 × 10 9 ) items day −1 . Their prevalence decreased from influent to final effluent. Overall abundances decreased on average by 6%, 68%, 92%, and 96% after the pre-treatment, primary, secondary, and tertiary treatment stages respectively, although considerable variability occurred throughout the year. Sufficient particles remained in the treated effluent to generate an average discharge of 2.2 × 10 7 (95% CI, 1.2 × 10 7 to 3.2 × 10 7 ]) particles day −1 to the recipient river. Secondary MPs were predominant, while primary MP abundances were minimal. Fibres comprised 67% of all items, followed by films (18%) and fragments (15%). Chemical characterisation confirmed the presence of different types of polymers, with polypropylene fibres and fragments most abundant (23%). This research informs understanding of how wastewater effluent may channel MPs to the natural environment and their composition, and helps understand control points for optimising advanced treatment processes. Graphical abstract: Image 1 Highlights: Average inflow rate of microplastics in wastewater was 8.1 × 10 8 particles day −1 . Fibres were the most abundant type of microplastic. FTIR-ATR analysis revealed polypropylene was the most abundant synthetic polymer. Tertiary treatment appears to remove 97% of influent microplastics. More than 1.2 × 10 7 particles day −1 may be discharged from the WWTP.